Анализ значимости психологических проблем с помощью субсенсорного тестирования - Луценко, Е.Л. (My University, 2015)
The article “Significant psychological problems analysis by the instrumentality of subsensory testing” of O. L. Lutsenko is devoted to find out what kind of psychological production is revealing by subsensor tachistoskopically presentation of semantic stimulus. The MindLatent program, psychological tests FPI, “Addiction attitudes test”, “Test of attitudes in motivation-need sphere”, “Gambling addition assessment method”, “Sexual addition assessment method”, “Suicidal risk questionnaire” and actual problems form were used as research methods. It has been found that MindLatent program for testing by subsensor presentation of semantic stimulus is revealed absolutely unconscious actual problems than it resembles a projective test.
Keywords: психофизиология; субсенсорное восприятие; тестирование; семантические стимулы